Misery merchants: a creative non-fiction on a private prison in South Africa - Hopkins, Ruth (My University, 2019)
I visited management prison for the first time in 2012, when I was following up on letters that inmates had sent to the Wits Justice Project (WJP), the organization I worked for. I returned to Mangaung prison many times and interviewed inmates, warders and several other sources. I accessed damming government reports that I had been stuffed under the carpet and leaked video footage of abuse. Mangaung Prison is a Public Private Partnership (PPP). A consortium of five shareholders signed a contract with the government in 2000 to build, run and maintain a private prison. The evidence I gathered showed the prison's riot team-also known as the "Ninjas" - taking inmates to either the hospital or the the isolation unit, where there are CCTV blind spots. There they would shock them with their electrified shock shields. Inmates were also being injected against their will with anti-psychotic drugs, often when they had no history of mental illness. The warders went on several strikes in August September 2023 and the chaos in the prison escalated to unknown heights. When the prison appointed unqualified staff to replace the absent workers, the state stepped in and took over.
A research report submitted in partial fulfilment of the Degree of Master of Arts (Creative Writing) in the School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2019
Keywords: Private prison in South Africa; Corruption; Torture; Department of Correctional Services; Anti-psychotic medicine